Translation of the Western term between the problems of definition and the implications of employment. The term hermeneutics as a model: La traduction du terme occidental : entre les problèmes de définition et les implications de l’usage. Le terme « herméneutique » comme modèle - fellah , kheireddine (Maalim, 2026)
Scientific terms are scientific keys and cognitive tools that either help in acquiring and establishing the sciences, or in transmitting and employing them. From this perspective, they are methodological necessities that regulate the relationship between cognitive concepts, define the features of thought and expression, and serve as units that achieve the purposes of understanding and communication. The term 'hermeneutics' is considered the cornerstone of interpretation in the West, as it has developed its cognitive mechanisms to understand existence, humanity, and heritage.